Penanganan Kredit Bermasalah Pada Perumda BPR Bank Gresik - Aprilia, Nur Fitri; Akhiruddin, Anita (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2024)
Credit facilities are one of the services offered by BPR Bank Gresik, a financial organization that offers banking services to its customers. In providing this credit, BPR Bank Gresik experiences credit risk, namely credit is offered with interest that cannot be returned in accordance with the agreement that has been approved by the creditor and debtor. In bank financial management, problematic credit, or non-functioning credit, is a big problem. BPR Bank Gresik experienced various levels of problematic credit over the last five years, from 2018 to 2022. Improper credit management can result in losses. This research aims to overcome problem loans at "Perumda BPR Bank Gresik" and determine the best action to resolve problem loans. To explain how to manage and identify problem loans in banks, this research uses a qualitative descriptive research methodology. The problem with loans, according to researchers' findings, is that many customers deliberately do not make payments, and bank workers often neglect supervision, resulting in an annual growth in the value of non-performing loans (NPL) of more than 5%. Therefore, to prevent problematic credit, PERUMDA BPR Bank Gresik should "further increase supervision" of the credit provided, taking into account the condition of the debtor and its management. Banks also consider the requirements of prospective customers before providing credit to prevent problematic credit.